Threat of war on cognitive development of refugee children - Yeter, Özlem; Rabagliati, Hugh; Özge, Duygu (East European Journal of Psycholinguistics, 2022)
War trauma is often accompanied by poor living conditions in the new environment in a manner preserving or even deteriorating the negative influences of war. Several researchers have investigated the refugee experiences of displaced children. Often they have focused on the detrimental effects of war on psychological well-being, mental health, educational settings, social adaptation, quality of nutrition, financial difficulties, safety and language learning experiences. Each of these effects has been proven to negatively affect cognitive abilities; however, the current study reviews the key studies to reveal the cognitive and linguistic outcomes of holding refugee status in the early childhood period. Doing this, we aim to reveal the adverse conditions that affect refugee children’s three core abilities of executive functions, namely working memory, inhibitory control and shifting. In addition to cognitive outcomes, we present the factors that may affect these children’s mother tongue development and their experiences with the language spoken in the host country in the context of schooling. This study suggests that refugee children should be assessed for their cognitive and language abilities after arriving in the country of resettlement so that their needs can be identified and addressed effectively. Caretakers should also be given both psychological and financial support to enrich their children’s language and cognitive input. Also, the outcomes of the research in this field should be effectively shared with different stakeholders from the caregivers and teachers of the refugee children to the NGOs and policymakers responsible to take solid actions to counter the adverse effects of displacement. Disclosure Statement No potential conflict of interest was reported by the authors.